2013
DOI: 10.1091/mbc.e13-01-0013
|View full text |Cite
|
Sign up to set email alerts
|

G protein–coupled receptor kinase 2 (GRK2) is localized to centrosomes and mediates epidermal growth factor–promoted centrosomal separation

Abstract: GRK2 is localized to centrosomes and regulates EGF receptor–promoted separation of duplicated centrosomes. This pathway depends on Mst2 and Nek2A and involves GRK2-mediated phosphorylation and activation of Mst2. Thus GRK2 plays a central role in mitogen-promoted centrosome separation via its ability to phosphorylate Mst2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…As the centrosomes separate further, more and more chromosomes become available to the MTs emanating from both poles, and this increases the chances of correct syntelic attachments due to symmetric outgrowth of MTs from both spindle poles [94]. In line with these observations and models [89,90,92,94,95], EGF-induced early centrosome separation promotes a faster mitotic progression with fewer chromosome segregation errors [92]. Induction of early centrosome separation either by addition of EGF to the medium or by expression of the EGFR decreases the requirement of Eg5 for mitotic progression [92].…”
Section: Timing Is Everythingsupporting
confidence: 61%
“…As the centrosomes separate further, more and more chromosomes become available to the MTs emanating from both poles, and this increases the chances of correct syntelic attachments due to symmetric outgrowth of MTs from both spindle poles [94]. In line with these observations and models [89,90,92,94,95], EGF-induced early centrosome separation promotes a faster mitotic progression with fewer chromosome segregation errors [92]. Induction of early centrosome separation either by addition of EGF to the medium or by expression of the EGFR decreases the requirement of Eg5 for mitotic progression [92].…”
Section: Timing Is Everythingsupporting
confidence: 61%
“…With the growing understanding of centrosome disjunction mechanisms, the reason for this observation was revisited with discovery that EGF regulates association of Nek2 with centrosomes via Mst2, Akt, and PI3K (Mardin et al, 2013 ). Further studies not only confirmed the role of Mst2 and Nek2 in EGF-mediated centrosome separation, but also demonstrated a role for the G-protein-coupled receptor kinase 2 (GRK2) in phosphorylating Mst2 in response to EGF (So et al, 2013 ). This occurs on two of three sites that are also phosphorylated by Plk1, hence Mst2 provides a point of integration of extracellular signals from EGFR with internal signals of mitotic progression from Plk1.…”
Section: Nek Kinases In Centrosome Disjunctionmentioning
confidence: 90%
“…Addition of EGF to the culture medium or overexpression of EGFR induces premature centrosome separation, presumably by activating the Mst2-Nek2A module in S phase (Mardin et al, 2013). G protein-coupled receptor kinase 2 (GRK2) has been found at centrosomes and may be involved in EGFR-mediated centrosome separation (So et al, 2013). Upon EGF addition, GRK2 phosphorylates and activates Mst2, leading to the initiation of centrosome disjunction.…”
Section: Centrosome Dynamicsmentioning
confidence: 99%